The effect of Astym® Therapy on muscle strength: a blinded, randomized, clinically controlled trial. Issue 1 (December 2015) - Kivlan, Benjamin; Carcia, Christopher; Clemente, F.; Phelps, Amy; Martin, RobRoy
Abstract Background Astym® therapy is a manual therapy intervention used to stimulate tissue healing, decrease pain, improve mobility, and improve muscle performance associated with musculoskeletal pathology. The purpose of this study was to determine if Astym therapy administered to the lower extremity would result in an immediate change of maximal force output during a unilateral isometric squat test among individuals with a lower extremity injury. Methods Forty-five subjects (14 males; 31females) between 18 and 65 years of age were randomized into 3 treatment groups: 1) Control group – received no treatment 2) Placebo group – received a sham Astym treatment 3) Astym therapy group– received Astym therapy to the lower extremity. A baseline measure of maximal force output (pre-test) during a unilateral isometric squat was performed. The subjects then received the designated treatment intervention. Immediately following the treatment intervention, maximal force output (post-test) was retested using identical testing procedures by an investigator who was blinded to the treatment intervention received by the subjects. The percent change of maximal force output from pre-test to post-test measures was compared using a one-way analysis of variance. A Tukey's post-hoc analysis determined the statistical differences between the groups. Results The treatment intervention had a significant effect on the percent change of maximal force output [F(2, 42) = 7.91, p  = 0.001]. Tukey's post hoc analysis demonstrated that the percent change of maximal force output was significantly greater in the Astym group (15 ± 18 % change of Newtons) compared to the placebo (−6 ± 11 % change of Newtons;p  = 0.0001) and control (−1 ± 17 % change of Newtons;p  = 0.0014) groups. No significant difference (p  = 0.68) was noted between the control and placebo groups. Conclusions Astym therapy to the involved lower extremity increased maximum force output during an isometric squat test immediately following treatment. The results of this study suggest that Astym therapy can immediately improve muscle performance (maximal force output) for patients presenting with muscular weakness caused by a lower extremity musculoskeletal injury. Trial registration Clinicaltrials.govNCT02349230 . Registered 23 January 2015.